2018
DOI: 10.1177/0165025418806584
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation during adolescence: Antecedent or outcome of depressive symptomology?

Abstract: Consistently, moderate to strong correlations between emotion regulation and depressive symptomology are well documented. This relationship is most often conceptualized as unidirectional, in that poor emotion regulation acts as a pre-existing risk factor for depressive symptomatology. However, explicit examinations of the direction of this relationship have been limited, and support for a directional relation between emotion regulation and psychopathology has been inconsistent. Moreover, the majority of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 71 publications
1
15
1
Order By: Relevance
“…In exploring a mediating process in which RS exerts flowon effects to internalising symptoms via ER-deficits, critical additional questions come to light. That is, within this RSinternalizing dynamic, bidirectional effects are possible, and indeed likely, as suggested by previous research (Compas et al, 2017;De France, Lennarz, Kindt, & Hollenstein, 2019;Masters, Zimmer-Gembeck, & Farrell, 2019). Specifically, ER-deficits and increased internalizing symptoms likely reciprocally influence each other over time, and so a full exploration of a longitudinal RS model includes testing these reciprocal effects.…”
Section: Bidirectional Associations: Emotion Regulation (Er)-deficimentioning
confidence: 73%
See 3 more Smart Citations
“…In exploring a mediating process in which RS exerts flowon effects to internalising symptoms via ER-deficits, critical additional questions come to light. That is, within this RSinternalizing dynamic, bidirectional effects are possible, and indeed likely, as suggested by previous research (Compas et al, 2017;De France, Lennarz, Kindt, & Hollenstein, 2019;Masters, Zimmer-Gembeck, & Farrell, 2019). Specifically, ER-deficits and increased internalizing symptoms likely reciprocally influence each other over time, and so a full exploration of a longitudinal RS model includes testing these reciprocal effects.…”
Section: Bidirectional Associations: Emotion Regulation (Er)-deficimentioning
confidence: 73%
“…However, much of the literature focused on child, adolescent and young adult ER and adjustment specifies this relationship as unidirectional (i.e., an ER-deficit direction of effects), indicating deficits in the habitual use of adaptive ER strategies, and overuse of maladaptive strategies, as risk factors for emotional maladjustment (Compas et al, 2017;Nolen-Hoeksema & Aldao, 2011;Perry-Parrish & Zeman, 2011;Thompson, 1994). That said, more recent longitudinal models underscore that the links between ER strategies and emotional maladjustment are likely to be bidirectional (De France et al, 2019;Larsen et al, 2013;McLaughlin et al, 2011), though a clear direction of effect remains unclear. For example, among one study assessing early adolescents over the course of 1 year (Larsen et al, 2013), and another over 2 years (De France et al, 2019), both found that depressive symptoms significantly predicted increases in expressive suppression over time, but not vice versa.…”
Section: Bidirectional Associations: Emotion Regulation (Er)-deficimentioning
confidence: 99%
See 2 more Smart Citations
“…Internalizing disorders are related to deficits in ER (Allen & Sheeber, 2009), and ER is often assumed to underlie mental health problems, but the direction of effects is not clear yet. Recent research showed some evidence that insufficient ER strategies precede depressive symptoms: habitual use of suppression preceded depressive symptoms in two adolescent samples (DeFrance, Lennarz, Kindt, & Hollenstein, 2016; Larsen et al, 2013). Knowledge about the short-term influence of ER strategies may contribute to resolving this important question by showing the (mal)adaptive effects of specific ER strategies in the short-term.…”
Section: Discussionmentioning
confidence: 99%